A laser photoacoutic imaging technique for the detection of small objects embedded in tissue - Zainal, Jasman (Faculty of Science, 2008)

(untitled)
We have applied a non-invasive photoacoustic technique to produce two-dimensional images of objects visually hidden within biological tissue. The technique has a foreseeable application for diagnosis of skin and subcutaneous diseases. We used a forward looking photoacoustic probe that integrated an optical-fibre laser pulse delivery system with a polymer transducer (PVDF) as a sensing element. The system’s frequency response was in the few MHz regions. The probe was designed to transmit laser pulses and detect returning ultrasonic waves from features within tissue. Tissue sample were prepared using fresh chicken breast. They contained a strand of human hair or hairs threaded into the chicken breast near the surface, serving as a foreign body. B-scan studies under normal saline solution were performed by scanning the PVDF probe across the chicken breast. Results revealed an image of the hair or hairs with a lateral resolution down to ~ 500(im and depth resolution of about ~80|im. Some images not only showed the presence of a foreign body within the tissue, but they also contained photoacoustic features that may indicate the cross-sectional dimension of a human hair.